Improved the stability and enhanced luminescence of Er doped CsPbBr3 perovskite. (15th November 2022) - Wang, Junfei; Wang, Fei; Luo, Yanwei; Li, Xiaodong; Jia, Yu
Abstract: Cesium lead bromide (CsPbBr3 ) perovskite has gained significance owing to its potential performance in optoelectronic devices. Here, using the first-principles calculations based on density functional theory, we investigate the effect of Er substitution on Pb atom position on the structural, electronic, and optical properties of CsPbBr3 for improving its luminescence properties. We show that the doping system with highest doping concentration yields the lowest negative binding energy, suggesting that Er doping can enhance the stability of CsPbBr3 well. The calculated band structures indicate that the CsPb1- x Er x Br3 system is a p -type semiconductor with the direct bandgap, and the bandgap increases with the increase of Er doping concentration. Interestingly, the Er defect levels obviously appear in bandgap, effectively decreasing the difficulty of the electronic transition. The density of states also show that there are more Er 4 f →4 f and less Er 4 f →Er 5 d electronic transition exiting in CsPb1- x Er x Br3 system, which are the main origins of luminescence enhancement for CsPbBr3 . Furthermore, the optical properties are also analyzed and they imply that the Er doping can improve the optical properties of CsPbBr3 in infrared phonon energy region, and nearly retain the optical properties of CsPbBr3 in other phonon energy region. Our work provides a new luminescence tunable design strategy for Er-doped perovskite materials for the optical communication application.